ANALYZING THE FACTORS THAT AFFECT THE AMOUNT OF PLASTIC WASTE - Mustika Sufiati Purwanegara; Anak Agung Ngurah Tata Pinandhika; Yang Sun; Regina Athalia (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2023)
One of the biggest environmental issues facing the planet today is plastic garbage, which was created by people and has an effect on them as well. Although though governments have implemented policies, rules, and other initiatives to increase public awareness of and engagement in decreasing plastic trash, the statistics has not changed, and this amount keeps rising every year. Several nations appear to be having trouble solving this problem. In addition, according to the World Bank, the country produces more plastics the wealthy its citizens are. By evaluating behavior and educating people, culture and education can be the answer to this problem. As people get more educated, their awareness of and care for the environment increases. The relationship between each of these factors—culture, education, national income, and government role and environmental problems might potentially help minimize plastic waste. Consequently, the goal of this study is to pinpoint the variables that may have an impact on the volume of plastic garbage and examine how these variables may affect the quantity of plastic waste in various nations. Hofstede's national culture dimension (Power Distance, Collectivism and Individualism, Masculinity and Femininity, Uncertainty Avoidance, Long-term Orientation and Short-term Orientation, Indulgence and Restraint), wealth per capita, education, and the government's plan and policy on sustainable consumption are the variables that will be examined. In this study, worldwide data for the year 2018 is gathered from 66 different nations utilizing secondary sources, and the data is then analyzed using the Multiple Linear Regression approach. According to the findings, there is a strong correlation between individualism and collectivism and the volume of plastic garbage. The results of this study should help each nation's government reduce the quantity of plastic garbage that is generated.